2004
DOI: 10.5194/angeo-22-2643-2004
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of ELF/VLF signals generated by modulated heating of the lower ionosphere with the HAARP HF transmitter

Abstract: Abstract.It is now well known that amplitude modulated HF transmissions into the ionosphere can be used to generate ELF/VLF signals using the so-called "electrojet antenna". Although most observations of the generated ELF/VLF signals have been made on the ground, several low and highaltitude satellite observations have also been reported (James et al., 1990). One of the important unknowns in the physics of ELF/VLF wave generation by ionospheric heating is the volume of the magnetosphere illuminated by the ELF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…439-442]. This determination is consistent with previous satellite measurements of radiation detected on satellites above a modulated ionosphere Platino et al, 2004].…”
Section: Fdtd Resultssupporting
confidence: 88%
“…439-442]. This determination is consistent with previous satellite measurements of radiation detected on satellites above a modulated ionosphere Platino et al, 2004].…”
Section: Fdtd Resultssupporting
confidence: 88%
“…ELF/VLF waves produced by auroral electrojet modulation with the HAARP facility were detected by the Cluster satellites at a radial distance of 27,000–29,000 km immediately outside the plasmapause [ Platino et al , 2004]. It is suggested that high magnetic activity might by necessary for the detection of HAARP‐generated ELF/VLF signals beyond L ∼ 4.…”
Section: Ionosphere‐magnetosphere Couplingmentioning
confidence: 99%
“…The generation of electromagnetic waves in the ELF/VLF frequency range by modulated HF heating of the ionospheric plasma has been the subject of many studies. Experiments and theory revealed that three completely different physical processes control their generation: (1) electrojet current modulation, which relies on modulated HF heating of the D/E region plasma electrons in the presence of electrojet currents, capable of VLF generation up to 10-20 kHz [Rietveld et al, 1986;Barr et al, 1985;Papadopoulos and Chang, 1985;Papadopoulos et al, 1990Papadopoulos et al, , 2003Papadopoulos et al, , 2005Platino et al, 2004Platino et al, , 2006Piddyachiy et al, 2008;Cohen et al, 2011;Cohen and Golkowski, 2013]; (2) ionospheric current drive [Papadopoulos et al, 2011a[Papadopoulos et al, , 2011b, which relies on modulated heating of the electron temperature in the F region, is independent of the presence of electrojet currents and capable of ELF generation up to 60 Hz; and (3) excitation of the thermal cubic nonlinearity is an additional electrojet-independent mechanism for generating ELF/VLF waves [Moore et al, 2013].…”
Section: Introductionmentioning
confidence: 99%